Negative-Pressure Wound Therapy in the Prevention and Management of Complications From Prosthetic Breast Reconstruction: A Systematic Review and Meta-analysis. Issue 4 (October 2021) - Chicco, Maria; Huang, Tony Chieh-Ting; Cheng, Hsu-Tang
Abstract : Background: Complications from prosthetic breast reconstruction are distressing for patients, and their management is challenging. For decades, negative-pressure wound therapy (NPWT) has been successfully used for the closure of complex wounds. This study analyzes the outcomes of NPWT use in the prevention and management of complications from prosthetic breast reconstruction. Method: A systematic search of studies published until August 2020 was conducted using the PubMed/MEDLINE, EMBASE, and Ebscohost/CINAHL databases and using the following key words: "negative-pressure wound therapy, " "breast reconstruction, " and "prosthesis" (including breast implants and tissue expanders). Analyzed endpoints were outcomes of NPWT use in prosthetic breast reconstruction compared with conventional dressings. The methodological quality of included studies was assessed independently. Comparative studies were further meta-analyzed to obtain pooled odds ratios (ORs) describing the effectiveness of NPWT in prosthetic breast reconstruction. Results/Discussion: Ten studies were included with a total of 787 patients (1230 breasts) undergoing prosthetic breast reconstruction with breast implants or tissue expanders. Three case-control studies focused on preventing breast wound complications. The meta-analysis of the 3 studies included 502 breasts receiving NPWT and 698 breasts receiving conventional wound care. The meta-analysis favored NPWT for less mastectomy flap necrosis (5.6% vs 14.3%; OR, 0.46; 95% confidence interval, 0.27 –0.77; P = 0.004; I 2 = 0%) and less overall wound complications (10.6% vs 21.1%; OR, 0.49; 95% confidence interval, 0.35–0.70; P < 0.00001; I 2 = 0%). In the management of nipple-areolar complex venous congestion, 1 case report demonstrated 85% rescue of nipple-areolar complex after using NPWT (−75 mm Hg) for a total of 12 days. In the management of periprosthetic infections, 2 case series used NPWT with instillation. It accelerated the treatment of infection and maintained the breast cavity for future reconstruction. Conventional NPWT also showed good salvage outcome in four studies. Conclusions: Current evidence suggests that prophylactic use of NPWT in prosthetic breast reconstruction reduces the rate of overall wound complications and mastectomy flap necrosis. In the management of complications from prosthetic breast reconstructions, NPWT may be a promising option showing beneficial results. Additional high-quality trials are warranted to corroborate the findings of this systematic review. Abstract : Supplemental digital content is available in the text.